Taxonomic revision of the Neotropical pirate spiders of the genus Gelanor Thorell, 1869 (Araneae, Mimetidae) with the description of five new species - Benavides, Ligia R.; Hormiga, Gustavo (Zootaxa, 2016)
We revise the Neotropical spider genus Gelanor Thorell, 1869 (Mimetidae). Gelanor is distributed from northeast Mexico to southern Uruguay , from sea level to 1,600 m. We describe five new species of Gelanor and report eleven new synonymies. Gelanor is here circumscribed to include ten species: Gelanor fortuna new species, Gelanor juruti new species, Gelanor moyobamba new species, Gelanor siquirres new species, Gelanor waorani new species, Gelanor altithorax Keyserling, 1893 (= Gelanor lanei Soares, 1941 new synonymy), Gelanor consequus O. P.-Cambridge, 1902 (= Gelanor depressus Chickering, 1956 new synonymy, Gelanor gertschi Chickering, 1947 new synonymy and Gelanor heraldicus Petrunkevitch, 1925 new synonymy), Gelanor innominatus Chamberlin, 1916, Gelanor latus (Keyserling, 1881) (= Gelanor mixtus O. P.-Cambridge, 1899 new synonymy, Gelanor mabelae Chickering, 1947 new synonymy, Gelanor ornatus Schenkel, 1953 new synonymy and Gelanor proximus Mello-Leitão, 1929 new synonymy) and Gelanor zonatus (C.L. Koch, 1845) (= Gelanor distinctus O-P. Cambridge, 1899 new synonymy, Gelanor insularis Mello-Leitão, 1929 new synonymy and Gelanor obscurus Mello-Leitão, 1929 new synonymy). In addition, we describe for the first time the males of G. altithorax and G. consequus. Species descriptions are provided for all ten species in the genus, together with a compilation of available data, including type specimens, type localities and morphological diagnoses. Light and electron microscope images and updated data on known geographical distributions, are also provided. We also discuss the phylogenetic placement of Gelanor in Mimetidae.